Peningkatan Keterampilan Guru Membuat LKPD Melalui Workshop Di SDN 026 Tanjung Selor - Hendri, Jhon (Universitas Cokroaminoto Yogyakarta, 2023)
The problem in this study is the low skill of teachers in making LKPD at SDN 026 Tanjung Selor. The research subjects were 8 teachers. Data collection techniques with observation and documentation techniques. Data analysis was performed using a comparative descriptive technique. The results of the observation assessment of discussion activities showed that in the initial conditions the score showed 45.94 in the LACK criterion and no teachers were declared complete, in the first cycle it increased to 68.75 in the SUFFICIENT criteria with 4 teachers or 50% declared complete, and in the end of the second cycle increased to 81.82 in the GOOD score qualification with 8 teachers declared complete (4 teachers or 50% in the VERY GOOD category and 4 teachers or 50% in the GOOD score criteria). From the research data in the activity it can be concluded that the Workshop on 8 teachers at SDN 026 Tanjung Selor was declared SUCCESSFUL in improving teacher skills in making LKPD